Digital financial literacy within the Telegram platform at the @sarjanacrypto community - Farabi, Muhammad Nabiel; Damayani, Ninis Agustini; Rodiah, Saleha (Faculty of Communication, Padjadjaran University, 2026)
Background: The crypto asset investment ecosystem on Telegram is characterised by extreme Information Velocity, which creates severe cognitive load, triggering irrational herding behaviour and exacerbating investor vulnerability to rampant misinformation.Purpose: This study analyses digital financial literacy as a cognitive defence mechanism against crypto misinformation within the Dark Social ecosystem of Telegram, specifically focusing on the @sarjanacrypto community.Methods: Employing a qualitative single-case study design, data were triangulated from online non-participatory observation, a thematic reduction of 3,974 archived Telegram messages, and in-depth interviews with seven informants spanning various market experiences.Results: Findings reveal how investors practice digital financial literacy to combat crypto misinformation. The results show that investors frequently engage in